Catatonia and Mutism: Neurotic, Psychotic, or Organic Disorder? - Pilar de Jaime Ruiz; Jose Luis García-Fogeda Romero; Luis Gutiérrez-Rojas (Case Reports in Psychiatry)
Background. Catatonia is caused by a variety of psychiatric and organic conditions. The onset, clinical profile, and response to treatment may vary depending on the underlying cause. Catatonia is more likely to be associated with neurotic and psychotic disorders, but some psychiatric symptoms are key components in the clinical presentation of other medical conditions. Case Report. We report the case of a woman who started showing paroxysmal recurrent episodes since the age of 57 years, characterized by surrounding disconnection, disorientation, and muscle spasm (myoclonus), followed by a postictal state. In the following months, the symptoms evolved to akinetic mutism, catatonia, and rapidly progressive vision and audition loss. She underwent a battery of tests, most of them inconclusive, until a neoplastic meningoencephalitis was diagnosed after more than two years of symptoms. Numerous medical conditions can mimic psychiatric disorders. This uncommon presentation may lead to a late diagnosis and treatment initiation, increasing significantly morbidity and mortality. A differential diagnosis with infectious, autoimmune, and neoplastic etiologies should always be carried out.